Frontiers of Semiconductor Lasers - Chen, Yongyi; Qin, Li (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Semiconductor lasers are carriers of both energy for industry and information for optical communications. The recent progress in research on semiconductor lasers has offered new perspectives regarding both their material growth and structural design. Most of the papers are review papers that briefly overview different types of semiconductors. Some of the papers include the newest research results. We all hope that this Special Issue can shed light on recent advances in the field of semiconductor lasers and their applications so that most of the readers' concerns about semiconductor lasers can be addressed and a conversation can be initiated.